Validity and internal consistency of the thoracic outlet syndrome index for patients with thoracic outlet syndrome - Vastamäki M.; Ruopsa N.; Vastamäki H.; Laimi K.; Ristolainen L.; Saltychev M. (Mosby Inc., 2025)
Background: No validated scales exist specifically for measuring quality of life (QoL) and functioning level in patients with thoracic outlet syndrome (TOS). This cross-sectional survey examined whether some items adopted from validated QoL scales could be suitable for patients with TOS.
Methods: To find an optimal thoracic outlet syndrome index (TOSI), a panel of 14 specialists experienced in treating TOS independently evaluated the relevance of 19 items adopted from scales used in other upper-extremity syndromes. After undergoing surgery for TOS, 52 patients rated the relevance of those items found by experts to be relevant. Content validity was measured by a content validity index, content validity ratio, and modified κ. The internal consistency of 15 retained items was assessed with the Cronbach α, and its construct validity was assessed by an exploratory factor analysis.
Results: Of the 19 items, 15 were considered relevant for TOS by the panelists, with an overall test content validity index of 0.93. The internal consistency of these 15 items was excellent. The exploratory factor analysis accompanied by a parallel analysis confirmed the uni-dimensionality of the TOSI. All 15 items that the panelists considered relevant were also items that the patients marked with scores over 7 points on an 11-point scale of relevance.
Conclusion: The internally consistent, face- and content-valid TOSI scale is proposed for use in evaluating specifically the QoL in TOS patients, as well as improving future longitudinal studies comparing functioning before and after interventions or spontaneous recovery in TOS patients.